Building Brands with Superheroes, Building Superheroes with Brands: The Brands of Iron Man and Captain America in the Marvel Cinematic Universe - Árpád Ferenc Papp-Váry; Áron Rönky (Businesses, 2025)
The use of product and service brands by popular movie characters has long been a powerful marketing tool, boosting brand awareness and enhancing brand image. Product placement—the appearance of brands in films—not only increases visibility but also provides vital financial support for film production, particularly in big-budget blockbusters. However, an interesting question arises: to what extent do filmmakers and brands align brand values with the personalities of film characters? Is the goal solely to maximize exposure, or is there a conscious effort to create authentic pairings that resonate with audiences? This study examines the appearance of product and service brands in the Marvel Cinematic Universe, focusing specifically on two main characters: Iron Man (Tony Stark) and Captain America (Steve Rogers). We analyzed 11 Marvel Studios films released between 2008 and 2019, documenting brand appearances and evaluating their alignment with the characters’ personalities. By applying personality typology models (Aaker, Mark and Pearson, MBTI, NERIS Type Explorer), we developed detailed profiles of both the movie characters and the associated brands. The findings reveal that while brand placements are extensive, there is often a deliberate effort to pair them with characters in ways that reinforce authenticity and strengthen audience connections. This benefits filmmakers, audiences, and brands alike by enhancing credibility and fostering emotional engagement.